A REVIEW OF JOB SATISFACTION SURVEYS IN HEALTH CARE - Milošević Gačević, Marijana (Srpski medicinski časopis Lekarske komore, 2022)
The healthcare sector is one of the sectors in the EU economy with significant employment potential, which is driven by the growing demand for healthcare. Job satisfaction contributes to the improvement of the quality of service, in every profession, and it is especially important in the field of work of professionals whose service should contribute to better and more efficient health care, and therefore it has been an important research topic for a number of years. The health care sector is facing many challenges. Therefore, providing a sufficient number of well-qualified and motivated staff will be a particular problem in countries facing a marked increase in the demand for health care. It is estimated that the shortage of health workforce will reach 12.9 million health workers by 2035. The health sector of the Republic of Serbia is facing similar challenges, but it also has its own specificities, conditioned by the historical, socio-economic, cultural, and political development of the country. This paper analyses the available literature on job satisfaction, factors influencing satisfaction, and challenges for improving job satisfaction in the health sector.
Keywords: job satisfaction; health care sector; challenges for improvement